Mythbusters united? A dialogue over Harris's integrationist linguistics and Gibson's Ecological Psychology. (May 2023) - Jones, Peter E.; Read, Catherine
Abstract: In this paper an integrationist linguist (Peter E Jones) and an Ecological Psychologist (Catherine Read) open a dialogue on the possibility of a productive relationship between the integrationist approach to language and communication of Roy Harris and James Gibson's Ecological Psychology of perceiving/acting/knowing. Within their own disciplinary contexts, each position is one of profound critique and innovation in relation to established and pervasive 'myths'. Specifically, Harris is concerned with the 'language myth'—the explicit positions and implicit assumptions in the Western language tradition (including modern linguistics) about the nature of language and the relationship between language and communication. In sharp contrast to mainstream approaches, Harris rejects both coding and representational views of meaning and takes signs (including linguistic signs) to be the product, rather than the precondition, of communicational activity. Similarly, Gibson critiques assumptions about how perception takes place, especially in the case of vision, that have informed Western science at least since Descartes' Optics . In particular, Gibson rejects the passive 'retinal image fallacy' of seeing in favour of an activity based non-representational perspective of 'direct perception'. The paper offers a critical dialogue over the key theoretical perspectives of both traditions, focusing particularly on the import and implications of each theorist's claims and assumptions about the other's field. Highlighting key areas of apparent common ground across the two approaches, we also argue that Gibson appears not to be entirely free of assumptions about language that belong to Harris's 'language myth', while Harris appears at times to assume the 'image' based model of perception that Gibson rejected. In the context of current interest in a possible reconciliation or combination of integrational linguistics and Ecological Psychology, the paper, therefore, raises fundamental questions around the extent to which these independently developed programmes of demythologization are compatible or possibly synergistic. Highlights: The possibility of a productive relationship between Harris's Integrational Linguistics and Gibson's Ecological Psychology is considered. Harris and Gibson both reject a traditional view of perception as involving the transmission of signs. Harris's integrational view of sign-making offers a perspective on communication that Gibson had not considered. Harris's views on perception appear to assume the 'retinal image myth' which Gibson rejected in favour of 'direct perception'.